Maldives : 2009 Article IV Consultation; Staff Report; Staff Supplements; Public Information Notice on the Executive Board Discussion; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Maldives. (IMF Staff Country Reports; Country Report, 2010)
This paper examines the Maldives' 2009 Article IV Consultation on economic developments and policies. The Maldivian economy is facing large external and fiscal imbalances, resulting from the severe impact of the global financial crisis and exacerbated by an unsustainable fiscal expansion. The global crisis has led to sharp declines in tourism and related investment, other net capital flows, and exports. This has caused a significant fall in fiscal revenue, compounding a large increase in public spending, and pushed the economy into recession. A rising share of the resulting fiscal deficit has been financed by monetization.